Detection of Financial Reporting Fraud: The Case of Socially Responsible Firms - Dedik Nur Triyanto (Journal of Economics, Business, and Accountancy Ventura, 2019)
This study aims to analyze the implementation of fraud pentagon theory, covering pressure, opportunity, rationalization, competence, and arrogance variables on financial statement fraud using the Beneish M-score method for socially responsible companies listed in the SRI-KEHATI index of the Indonesia Stock Exchange in the period 2013-2018. The secondary data were taken from the annual reports and audited financial statements of companies. The sample was selected using a purposive sampling in which 13 SRI-KEHATI index companies as the sample with a four-year research period in 2013-2018, a totally of 78 samples. The data were analyzed using descriptive statistical analysis and logistic regression analysis using IBM SPSS statistical software 25. The results showed financial targets, ineffective monitoring, and the nature of the industry, changes in directors, and the frequency of the appearance of CEO photos simultaneously influencing financial statement fraud. Partially, ineffective monitoring, changes in directors and the frequency of CEO photos on fraudulent financial statements have a negative effect, and the nature of the industry has a positive effect, while financial targets do not affect financial statement fraud. This research can be used as a reference for stakeholders in the company to consider the proportion of independent directors and the ratio of receivables in detecting fraud in a company.